(untitled) (The Research of Medical Science Review, 2025)
Antimicrobial resistance (AMR) has emerged as a significant global health issue, compromising the efficacy of antimicrobial medicines essential for human and veterinary therapy. The veterinary sector, especially animal production systems, significantly contributes to the emergence and spread of resistant infections owing to the prevalent and frequently unregulated use of antibiotics. Resistant organisms and resistance genes can be transmitted to humans through foodborne exposure, direct contact with animals, or environmental routes, thereby exacerbating the public health burden. The One Health concept has emerged as a comprehensive framework for managing antimicrobial resistance (AMR) owing to its recognition of the multisectoral nature of the issue at the junction of human, animal, and environmental health. This review analyzes the epidemiology and primary factors contributing to antimicrobial resistance (AMR) in veterinary contexts, including antimicrobial overuse, insufficient stewardship, and environmental contamination. It further examines the ramifications of veterinary antimicrobial resistance on public health, emphasizing zoonotic transmission, occupational hazards, and environmental reservoirs. This review defines global and national One Health policies focused on surveillance, policy integration, and antimicrobial stewardship, while highlighting significant implementation gaps, especially in low- and middle-income nations. Challenges, including fragmented governance, inadequate diagnostic capacity, inadequate regulatory enforcement, and insufficient awareness, persist and hinder advancement. The review asserts that effective mitigation of AMR necessitates continuous investment, coordinated intersectoral collaboration, and tailored strategies. Enhancing veterinary surveillance systems, advocating for appropriate antibiotic utilization, and driving research into alternatives are critical elements of an effective One Health response. In the absence of such coordinated initiatives, antimicrobial resistance will persist, jeopardizing animal productivity and public health safety.